Evolution of the Forms of Threats to the Inviolability of Property Rights during Interstate Military Conflicts - YAROTSKIY, Vitaliy; SPIESIVTSEV, Denys (Journal of Advanced Research in Law and Economics, 2019)
The research is devoted to consideration main forms of threats to the inviolability of property rights during interstate military conflicts in context of evolution of legal approaches to appropriate problem. It is determined that throughout the evolution of mankind, the escalation of inter-state agreement relations was often accompanied by the emergence of threats to property rights as of the member states of relevant local conflicts, as well as of individuals and legal entities whose property was located in the territory of the conflicting states. The nature of these threats has changed during the development of our civilization and is often accompanied by direct encroachments on property owned by the state involved in the conflict or owned by private individuals who fall within its jurisdiction or legally residing in its territory. And only in some cases, during these conflicts, the recognition of the inviolability of private property was guaranteed, while limiting the legal grounds for acquiring the property of the enemy state with the creation of effective mechanisms for national and international protection of such rights. Considerable attention is paid in the article to each stage of evolution of the forms of threats to the inviolability of property rights during interstate military conflicts and their features are analyzed. The paper shows how proprerietary relationships between common citizens and juridical persons correlate with property relationships between states during military conflicts.